التبني والكفالة بين الفقه والتشريع الجزائري - مصباحي, سندس (جامعة الوادي -University eloued, 2017)
التبني هو إلحاق ابن الغير كابن غير شرعي وإلحاق نسبه له ومنحه كل حقوق الابن الشرعي, وهو نظام قديم عرفته البشرية قبل ظهور الإسلام وقد حرمه هذا الأخير. والمشرع الجزائري وافق الشريعة الإسلامية في تحريمه بنص المادة 46 من قانون الأسرة الجزائري, استبدل التبني بنظام الكفالة الذي حثت عليه الشريعة الإسلامية وهو رعاية اليتيم ومعاملته بالبر والإحسان. حرصت على حماية حقوقه وبشرت على من يقوم بذلك مصاحبة النبي (ص) وشددت العقاب على من يهين أو يقهر اليتامى ومنحت المكفول حقوقا على من يكفله ورخصت له الولاية على نفسه وماله وهو ما وافقها عليه المشرع الجزائري في المواد من 116 إلى 125 من قانون الأسرة الجزائري الذي يسن أحكام الكفالة, التي هي رعاية المكفول واشترطت في ممارستها العقل والقدرة العقلية والمالية, ويمكن للكفالة أن تنتهي بالرغم من أنها عقد غير وقتي لكنه ذو طابع إنساني أساسه التقرب إلى الله.Adoption is the appendage of the son of others as an illegitimate son and to attach a percentage to him and grant him all the rights of the legitimate son, an ancient system known to mankind before the advent of Islam has been deprived by the latter. The Algerian legislator approved the Islamic shariah by banning article 46 of the Algerian Family Code, replacing the adoption of the kafala system, which was encouraged by Islamic law, which is to care for the orphan and treat him with righteousness and charity. (P) and tightened the punishment on those who humiliated or oppressed the orphans and granted the sponsored rights to those who sponsored him and authorized him the mandate for himself and his money, which was approved by the Algerian legislator in Articles 116 to 125 of the Algerian Family Code Which establishes the provisions of bail, which is the care of the sponsored and stipulated in the practice of mind and mental and financial ability, and can be guaranteed to end, although it is a contract but a time of a humanitarian nature based on proximity to God
ماستر أسرة
Keywords: التبني ،الكفالة ، الفقه ،التشريع ،الجزائري; Adoption, sponsorship, jurisprudence, legislation, Algerian